(untitled) (Advancements in Homeopathic Research, 2025)
Allergic contact dermatitis is an inflammatory skin condition caused by a type 4 hypersensitivity reaction. It occurs when an irritant or allergen comes into contact with the skin, triggering a T-cell mediated response. The appearance and location of the dermatitis often help identify the causative agent. For example, dermatitis around the wrist might indicate an allergic reaction to a bracelet or watchband.1 In this case report we present a case of allergic contact dermatitis, presenting with complaints of severe itching and burning on left dorsum of hand with cracks and dryness of skin, bloody discharge on scratching for 2 months, itching aggravated in cold weather. After complete case taking and proper repertorisation, on the basis of totality of symptoms Petroleum 30 was prescribed.